Pemberdayaan Masyarakat Melalui Pelatihan Budidaya Microgreen di Desa Kesilir, Kecamatan Wuluhan, Kabupaten Jember - Tri Rini Kusparwanti; Refa Firgiyanto; Gallyndra Fatkhu Dinata; Fadil Rohman (Journal of Community Development, 2022)
Kesilir Village is one of the villages in Wuluhan District, Jember, East Java with the majority of the population's main livelihood being farmers. One of the youth organizations active in the village is IPNU-IPPNU Kesilir. Most of the organizations that consist of Muslim youths are aged 15-21 years. Based on the problems obtained in the results of the preliminary survey, it was found that there were problems with the youth of the community, including the community's desire to optimize the use of abundant resources in the form of the agricultural sector in Kesilir Village and the solution that we offer to the youth of the Kesilir Village community is in the form of making microgreens As a first step for learning the modern agricultural sector, socialization about microgreens for IPNU-IPPNU Kesilir. The method used is Participatory Rural Appraisal (PRA) which is an approach method in the process of empowerment and increasing community participation that emphasizes the involvement of IPNU-IPPNU Kesilir in all activities carried out. The techniques used in Participatory Rural Appraisal (PRA) include the socialization stage, skills training stage and mentoring stage. This activity resulted in socialization of training on making microgreens, and making direct products consisting of microgreens of water spinach and mustard pakcoy. IPPNU-IPPNU youths were provided with a simulation of microgreens cultivation which is easy to do and has high economic value. From this community service, it is hoped that the IPPNU-IPPNU Kesilir will be the pioneers of microgreen cultivation in Kesilir Village, Wuluhan District, Jember. In addition, this activity can be a promising business opportunity because it has a high profit which is expected to be carried out by young people in Kesilir Village, Wuluhan District, Jember.